Efficient Parallel FDTD Algorithm for Modeling Infinite Graphene Sheet Simulations - Ramadan, Omar (IEEE, 2017)
Graphene, which is considered to be an infinitely thin two-dimension material, is a very promising optoelectronic material and has received much attention due to its outstanding electrical and optical properties. This paper describes an efficient message-passing interface (MPI) parallel implementation of the finite difference time domain (FDTD) algorithm for modeling infinite Graphene sheet simulations. The algorithm, which is based on the domain decomposition approach, reduces the number of field components to be exchanged between the neighboring processors as compared with the conventional parallel MPI FDTD implementation. Numerical simulations are included to show the effectiveness of the proposed parallel algorithm.
8th International Conference on Information and Communication Systems (ICICS) -- APR 04-06, 2017 -- Irbid, JORDAN
Keywords: Parallel programming; message passing interface (MPI); finite difference time domain (FDTD); domain decomposition; Graphene